ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGERAKAN HARGA SAHAM DI BURSA EFEK INDONESIA - Sriyono, Heru (Sosio e-kons, 2014)
This study aims to determine the effect of simultaneous and partial Earning per Share, Price Earning Ratio, Book Value per Share, Debts to Equity Ratio dan Dividen Payout Ratio on Stock Price. The research method used is the method of documentatio, sample totaling 25 companies listed in Indonesia Stock Exchange are included in LQ45. The collection of data collected from secondary data published by the Indonesia Stock Exchange, a data analysis technique used is regression analysis techniques. Statistical tests using the F test and t test. Data were analyzed using correlation and regression techniques. From the results of the study found that: (1) There is the influence of EPS on the stock price (Riy 0.60, KD = 36%, Y = 94 094 + 6,298X1). 2) There is the influence of the Price per Share (Ry2 = 0.46, KD = 21% Y = 534.223-26.100X2). 3) There is no influence on Stock Price BVS (Ry2 = 0.005, KD = -5% Y = 0.005 120.447- X3). 4) There is the effect of DER on Stock Price (Ry2 = 0.334, KD = 11.1% Y = 227955-30.064X4). 5) There is the influence of the House of Representatives on Stock Price (Ry2 = 0.657, KD = 43.2% Y = 524-11.486X5). 6) There is the influence of EPS, PER, DER and the House of Representatives on Stock Price (ry12 = 0.993, KD = 98%). ^Â Y = 1080.156 - 6.441X1 - 13 558 0,059 X2 + X3 - 305 19. 1488 x4 + x5